Advanced imaging findings in progressive solitary sclerosis: a single lesion or a global disease?. Issue 1 (January 2019) - Lee, Lisa Eunyoung; Chan, Jillian K; Nevill, Emilie; Soares, Adam; Vavasour, Irene M; MacMillan, Erin L; Garren, Hideki; Clayton, David; Keegan, B Mark; Tam, Roger; Traboulsee, Anthony L; Kolind, Shannon H; et al.
Background: Progressive solitary sclerosis is a unifocal demyelinating disease recently proposed as a possible multiple sclerosis variant. Objective: To compare myelin content and brain metabolite ratio qualitatively in the normal-appearing white matter of progressive solitary sclerosis cases compared to multiple sclerosis and healthy control participants. Methods: Case report. Results: Progressive solitary sclerosis cases showed abnormal myelin in normal-appearing white matter tracts and global normal-appearing white matter as well as lower N-acetyl-aspartate to total creatine ratio compared to multiple sclerosis and healthy control groups. Conclusion: Despite a single demyelinating lesion along the corticospinal tract in progressive solitary sclerosis, we showed evidence of more extensive abnormality within the normal-appearing white matter.